Recycle cold energy of liquid oxygen to clear carbon dioxide for AIP submarine - Wenbo PENG; Shi ZHANG; Zhiyin LI; Yao ZHANG (Zhongguo Jianchuan Yanjiu)
ObjectiveAir-independent propulsion (AIP) submarines carry huge quantities of liquid oxygen. However, in the liquid oxygen combustion process, the cold energy is not usually recovered, and there are criticisms concerning CO2 removal in the confined space of a submarine. Aiming at the two major pain points that have long plagued AIP submarines, this paper proposes an integrated solution that organically combines the recovery and utilization of cold energy from liquid oxygen with the removal of CO2 . Method Liquid oxygen can be used as a cold energy source to process the cabin air. According to the different phase transition temperature characteristics of each air component, the CO2 in the air is frozen (condensed) and separated under normal pressure. ResultsThis study uses quantitative data analysis to show that the energy stored in liquid oxygen can basically meet the cold energy demand for freezing the CO2 produced by the crew's respiratory metabolism within the self-sustaining capacity of the submarine, and proposes a three-level workflow and implementation plan. ConclusionThe technical solution proposed in this paper can recycle 5% of cold energy from liquid oxygen, which conforms to the idea of the comprehensive integration of energy saving and noise reduction, and the full integration of overall resources. As such, it can be used for air purification and CO2 removal in confined spaces such as submarines, submersibles and deep-sea space stations powered by AIP systems.